Uma contribuição à pirólise de biomassa: avaliação de alguns resíduos da agroindústria como fonte de energia alternativa - Kimura, Lygia Maestri (2009)
Factors such as global climate change, environmental pollution and reduction of the availability of fossil energy resources make renewable energy a topic of growing importance, and in this context biomass has been considered the major current source of clean energy. Among the technologies of energy conversion from biomass, pyrolysis is a promising tool as it generates products with high energy content in solid (charcoal), liquid (bio-oil) and gas phases. These products have diverse application: energy production, refinery input and in the preparation or activated charcoal (solid product). In the context presented, this work investigates the reaction of pyrolysis of some residues of Brazilian agribusiness (cashew nut shells, sugarcane straw, chicken litter and sawdust) as a way to obtain products of higher energy level. For that, the samples were pyrolyzed in a stainless steel reactor externally heated. The effect of varying temperature and pressure on yield and quality of the products obtained from cashew nut shells was investigated. For the other biomass, the reaction was performed at different temperatures: 300 C, 400 ° C, 500 º C, 600 º C and 700 º C at atmospheric pressure. The products obtained were charcoal, bio-oil, aqueous phase and pyrolytic gas. The experimental results showed that the increase in pyrolysis temperature resulted in decreasing yield of solid product obtained. The yield of charcoal ranged between (19.83 - 27.61) % for cashew nut shells, (27.65 - 47.35) % for sugarcane straw, (37.13 - 53.38) % for chicken litter and (26.86 - 45.29) % for sawdust. The highest oil yield was obtained at 500 ° C for chicken litter (9.50 wt.%) and sawdust (10.00 wt.%). The yield of biooil from cashew nut shells reached its peak at 600 º C (37.83 wt.%). Sugarcane straw produced no measurable amount of oil in the reaction conditions studied.